Konsep dan Sistem Nilai dalam Implementasi Model Cognitive Moral Development bagi Pendidik pada Pembelajaran Abad-21: Concepts and Value Systems in the Implementation of Cognitive Moral Development Models for Educators in 21st Century Learning - Fikriyah Fikriyah; Deni Setiawan; Aiman Faiz; Fifi Angguntriani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Quality improvement in instilling moral values and character in the world of education is an obligation today. The paradigm of character education by prioritizing violence still often occurs in educational practice in Indonesia, so appropriate solutions are needed to instill character values in elementary schools. This service was carried out at SDN 4 Kenanga by inviting participants of 50 elementary school teachers in the Sumber and Plumbon Districts. The implementation of the research consists of the preparation stage, implementation stage, monitoring, and evaluation stage. The service results show an increase in understanding of concepts and practices in the cognitive moral development model through the digital animation story method after the workshop. This activity concludes that this service has achieved the target of transmitting knowledge of the concept of value systems and character education models needed by elementary school teachers in 21st-century learning, which is expected to be a solution in moral and character education. The teacher has also implemented an action strategy model of cognitive moral development by the criteria for elementary school students.